SHORT TERM RESULTS OF TRANSCATHETER AORTIC VALVE REPLACEMENT WITH TRANSAORTAL APPROACH - A. V. Bogachev-Prokofiev; R. M. Sharifulin; D. D. Zubarev; I. Yu. Zhuravleva; A. M. Karaskov (Российский кардиологический журнал)
Aim. Transcatheter replacement of the aortic valve with transfemoral approach is the procedure of choice in patients with aortic valve defects and high to very high operatrional risk. If transfemoral approach is not applicable, alternative approaches implemented. The most rarely used is transaortal approach. The data was analyzed, of the direct transaortal approach for aortic valve replacement.Material and methods. During the years 2015-2017, 11 procedures performed, of transcatheter aortic valve replacement, with transaortal approach. In 10 cases, the operation was done with the right-sided anterior minithoracotomy, in 1 — with ministernotomy.Results. Thirty-day mortality was 9,1%. There were no conversions of surgical approach. In one patient (9,1%) there was paraprosthesis regurgitation, in the other — no such regurgitation, or non-significant. There were no hemorrhagic complications or complications of the surgery. One patient received permanent pacemaker for developed complete atrioventricular block.Conclusion. Direct transaortal approach makes it to safely and effectively perform transcatheter implantation of aortic valve and might be an alternative in the cases of impossible transfemoral approach.